DIE LERNERGEBNISSE DER DEUTSCHEN SPRECHFERTIGKEIT DURCH SRATEGIE PRACTICE-REHEARSAL PAIRS VON DEN SCH?LERN KLASSE XI IPA 4 AN DER SMAN 3 KEDIRI - M.VENIGRATIA SAO, MARIA (LATERNE, 2014)
Based Introduction Program (PPL ) in SMAN 3 Kediri academic year 2012/2013 , on learning conversational skills are not all active students in learning . Speaking skills learning outcomes can be said to be less satisfactory because student learning activity is very less in learning speaking skills . Therefore , the strategy used in this study - Rehearsal Practice Pairs to practice their speaking skills . This study examines the learning outcomes German speaking skills through strategies Practice-Rehearsal Pairs. Strategy Practice - Rehearsal Pairs is a simple strategy that is used to practice a skill or procedure with a study buddy . The goal is to perform the skills correctly ( Hisham Zaini, 2008:81 ). The problems of this research is how the results of learning German language speaking skills through strategies Practice - Rehearsal Pairs of students of class XI IPA 4 SMAN 3 Kediri ? While the purpose of this study was to describe the outcomes of learning German language speaking skills through strategies Practice - Rehearsal Pairs of students of class XI IPA 4 SMAN 3 Kediri . This research is descriptive quantitative . Data were obtained from tests of student learning outcomes in the form of pre-test and post -test . The data is then described later study concluded . The results obtained from the study of learning before and after learning through strategy - Rehearsal Practice Pairs , with the breakdown as follows : From the pre-test score showed only 26.66 % of the number of students who have met the KKM ( Minimum completeness criteria ) or as many as 8 students with an average of 50.00 were categorized as low grade . While the Post - test results showed 93.33 % of the number of students who have met the chief engineer or as many as 28 students with an average of 90.00 is considered high grade . Based on these data it can be seen that there is a better change of student learning outcomes in the German speaking skills . From the results of these studies indicate that the strategy Pracice - Rehearsal Pairs can be used by teachers as a variety of exercises in German language speaking skills . Keywords : Rehearsal Practice – Pairs, speaking skills.